Exploring Computational Thinking Skills Training Through Augmented Reality and AIoT Learning - Lin, Yu-Shan; Chen, Shih-Yeh; Tsai, Chia-Wei; Lai, Ying-Hsun (Frontiers in Psychology, 2021)
Given the widespread acceptance of computational thinking (CT) in educational systems around the world, primary and higher education have begun thinking about how to cultivate student’s CT competences. The artificial intelligence of things (AIoT) combines artificial intelligence (AI) and the Internet of things (IoT), and involves integrating sensing technologies at the lowest level with relevant algorithms in order to solve real-world problems. Thus, it has now become a popular technological application for CT training. In this study, a novel AIoT learning with Augmented Reality (AR) technology was proposed and be explored the effect of CT skills. The students used AR applications to understand AIoT applications in practice, attempted the placement of different AR sensors in actual scenarios, and further generalized and designed algorithms. Based on the results of the experimental course, we explored the influence of prior knowledge and usage intention on students’ CT competence training. The results show that proposed AIoT learning can increase students’ learning intention and that they had a positive impact on problem solving and comprehension with AR technology, as well as application planning and design.